Endovascular and hybrid therapies for structural heart and aortic disease - Kpodonu, Jacques; Bonan, R. (Wiley-Blackwell, 2013)
"Despite the "hot topic" status of this subject, there are few book-length resources that cover the subjects presented here in any depth. There is a particular need for high-quality coverage of hybrid techniques, which have emerged only over the last 3-4 years. Some of the techniques/procedures covered in this book have gained approval and are being used in patient care in Europe and elsewhere and are sure to see approval soon in the United States. Thus, this book not only fills a current need, but also anticipates a very likely near-term need amongst its target audience. The book aims to be a clear, practical guide to the topics covered, and with its combination of text with high-quality still images and videos presented on a companion website it should more than meet the expectations of buyers looking for expert guidance in this area"--Provided by publisher.